Методика розрахунку видування ¹³⁷Cs у чорнобильській зоні відчуження після природних пожеж - Ващенко, Володимир Миколайович; Сидоренко, Володимир Леонідович; Кордуба, Ірина Богданівна (НТУ "ХПІ", 2016)
Наведено модель дефляції (вітрового переносу) радіоактивних продуктів згоряння після природної пожежі у Чорнобильській зоні відчуження, що використовується для розрахунку горизонтальної міграції радіонуклідів у вигляді модуля дефляції. Запропонована методика розрахунку переносу еолового матеріалу, в якому містяться радіонукліди. Звертається також увага на те, що вогняні смерчі, які часто утворюються в зонах пожеж, є особливим маловивченим явищем, здатним створити небезпечну радіаційно-екологічну ситуацію шляхом інтенсивного підйому радіоактивних субстанцій на значні висоти та перенесення їх із зони пожежі на значні відстані.

This paper presents deflation (wind blowing) model of radioactive burning products after a wildfire in Chernobyl alienation zone. This model is used to calculate horizontal migration of nuclides as a deflation module. Based on existing models and experimental study of cesium-contaminated radionuclides deflation, a method for calculating eolic material transport containing radionuclides is proposed. Atmosphere radioactive contamination after radionuclides-contaminated forest fires is estimated by model forecast of radionuclides transport after wildfire and experimental data on ¹³⁷CS deflation intensity and their ratio. The development of model of radiocesium wind blowing into the air after a wildfire is based on requirement that it must disclose deflation nature, first of all, concerning ¹³⁷CS specific activity, maximal wind speed, dust storms durations, etc. Insensitivity and direction of ¹³⁷CS horizontal migration are linked to wind speed, its dynamic characteristics, soil susceptibility to deflation, degree of soil protection from wind, soil stability, vegetation availability, relief peculiarities, weather conditions and other factors. It is also stressed that firestorms, which often occur in wildfire regions, are a special understudied phenomenon that can cause a hazardous radiation-ecological situation by intense uplift of radioactive substances to significant heights and transport them from wildfire area to large distances that will subsequently cause radioactive conamination of areas outside the forest fires region.
The method of calculation blowing ¹³⁷Cs in Chernobyl alienation zone after wildfires
Keywords: чорнобильська зона відчуження; природні пожежі; радіоцезій; дефляція; видування; вогняний смерч; Chernobyl alienation zone; wildfires; cesium; deflation; blowing out; firestorm